THE ROLE OF HEALTH LITERACY IN PREDICTING PATIENT SATISFACTION WITH HEALTH CARE - Silkane, Vineta; Davidsone, Agnese; Veliverronena, Linda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Patient satisfaction has become one of the central indicators to measure quality of provision of health care services. However, it has been made clear in previous literature that the effectiveness and efficiency of the health care services is not directly proportional to the satisfaction level, because an array of patient’s personal, psychological, and cognitive factors such as beliefs, expectations, knowledge and others may come into play. In this current article, we report on a study aiming to examine the role of health literacy in predicting patient satisfaction with health care in Latvia. In summer-autumn 2017, data were collected from a random sample of 451 participants (44 % male) in age from 18 to 81 years. The participants filled-in the questionnaire consisting of: Patient Satisfaction Questionnaire (PSQ-III, Ware, Snyder, & Wright, 1976) and European Health Literacy Survey Questionnaire (HLS-EU-Q, HLS-EU Consortium, 2012). We measured four out of the seven aspects of PSQ, namely, general satisfaction, technical quality, interpersonal aspects, and communication. HLS-EU-Q contains three subscales: health care, disease prevention, and health promotion. Study results confirm that one of the health literacy aspects - health care - was the most important predictor of all patient satisfaction aspects, while health promotion predicted technical quality.